Effect of morphological characteristics of aggregate on the performance of pervious concrete. (27th February 2023) - Wu, Shuyin; Wu, Qiulin; Shan, Jingsong; Cai, Xing; Su, Xing; Sun, Xiaofeng
Highlights: Sphericity was used to describe the aggregate morphology. Effect of aggregate morphology on performance of pervious concrete was studied. Uniaxial penetration test was used to evaluate the aggregate skeleton. Single-phase seepage test and simulation were conducted. Abstract: The aggregate morphology plays a vital role in the performance of pervious concrete. This study investigates the effect of aggregate morphology on the mechanical properties and permeability characteristics of pervious concrete. Sphericity was selected as the index for describing the aggregate morphological characteristics using computed tomography (CT) and digital image processing (DIP) technology. Mechanical and single-phase seepage tests and simulations were conducted by Avizo software. The results show that the aggregates with more edges and corners are more favorable for forming an interlocking skeleton. With the addition of angular rich aggregates, the internal void distribution becomes more uniform, the equivalent pore size decreases, and the load-bearing capacity increases. The compatibility of particle morphology has an important influence on the properties of mixtures. As aggregate sphericity rises, the number of seepage paths reduces, the curvature of seepage channels improves, and the seepage velocity decreases. Based on the test results, the mechanical properties and permeability characteristics of pervious concrete can be optimized depending on engineering requirements by regulating the aggregate morphology.